Predicting Travel Times of Bus Transit in Washington, D.C. Using Artificial Neural Networks - Arhin, Stephen; Manandhar, Babin; Baba-Adam, Hamdiat (Salehan Institute of Higher Education, 2020)
This study aimed to develop travel time prediction models for transit buses to assist decision-makers improve service quality and patronage. Six-monthsâ€™ worth of Automatic Vehicle Location and Automatic Passenger Counting data for six Washington Metropolitan Area Transit Authority bus routes operating in Washington, DC was used for this study. Artificial Neural Network (ANN) models were developed for predicting travel times of buses for different peak periods. The analysis included variables such as length of route between stops, average dwell time and number of intersections between bus stops amongst others. Quasi-Newton algorithm was used to train the data to obtain the ideal number of perceptron layers that generated the least amount of error for all peak models. Comparison of the Normalized Squared Errors generated during the training process was done to evaluate the models. Travel time equations for buses were obtained for different peaks using ANN. The results indicate that the prediction models can effectively predict bus travel times on selected routes during different peaks of the day with minimal percentage errors. These prediction models can be adapted by transit agencies to provide patrons with more accurate travel time information at bus stops or online.Â Doi: 10.28991/cej-2020-03091615 Full Text: PDF